Antibacterial Activity of Haslea ostrearia Supernatant Adapted in Indonesia against Pathogenic Bacteria Relevant to Mariculture (In-Vitro Study) - Ikfa Permatasari; Fiddy Semba Prasetiya; Sulastri Arsad; Mochamad Untung Kurnia Agung; Jean-Luc Mouget (Journal Omni-Akuatika, 2019)
Haslea ostrearia has known as the only diatom which synthesizes a water-soluble blue pigment, marennine. It has some biological activities such as allelopathy, antioxidant, antibacterial, antiviral, and growth inhibitor. Marennine is available in two forms, intracellular which located in the apical of the cell and extracellular which released into the culture medium. This research aimed to test the bioactivity of Haslea ostrearia supernatant adapted in Indonesia as an antibacterial against pathogenic bacteria relevant to marine culture using in-vitro study. This research was using an explorative method, data analysed statistically and descriptive-comparatively observed. Observation parameters were the inhibitory zone of antibacterial activity, absorbance value of MIC test, and bacterial growth qualitatively from MBC test. Marennine concentration in the supernatant of Haslea ostrearia adapted in Indonesia is about 3.74 mg. L-1. The highest concentration supernatant of Haslea ostrearia that shown antibacterial activity is 3.5 mg. L-1 with inhibitory zone diameter is about 6.87 mm for Staphylococcus aureus and 7.14 mm for Vibrio harveyi, correspondingly. The minimum concentration that inhibits the growth of Staphylococcus aureus is 0.03 mg. L-1, while for Vibrio harveyi is 0.06 mg. L-1. Antibacterial activity of supernatant Haslea ostrearia originally adapted in Indonesia classified into bacteriostatic